2016
DOI: 10.1016/j.reprotox.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A review of the carcinogenic potential of bisphenol A

Abstract: The estrogenic properties of bisphenol A (BPA), a ubiquitous synthetic monomer that can leach into the food and water supply, have prompted considerable research into exposure-associated health risks in humans. Endocrine-disrupting properties of BPA suggest it may impact developmental plasticity during early life, predisposing individuals to disease at doses below the oral reference dose (RfD) established by the Environmental Protection Agency in 1982. Herein, we review the current in vivo literature evaluatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
238
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(249 citation statements)
references
References 132 publications
(170 reference statements)
1
238
0
10
Order By: Relevance
“…Thus, these preliminary studies suggest that low‐dose BPA has the potential to pose health hazards. Recent studies have also aimed to evaluate the role of BPA in carcinogenesis,7, 22, 23 and have indicated that exposure to BPA may account, at least partially, for the increased incidence of multiple cancers, including breast cancer,24, 25, 26, 27 ovarian cancer,28, 29 uterine cancer,30 prostate cancer,31, 32 testicular cancer,33 and liver cancer 34. The carcinogenic effects of BPA are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these preliminary studies suggest that low‐dose BPA has the potential to pose health hazards. Recent studies have also aimed to evaluate the role of BPA in carcinogenesis,7, 22, 23 and have indicated that exposure to BPA may account, at least partially, for the increased incidence of multiple cancers, including breast cancer,24, 25, 26, 27 ovarian cancer,28, 29 uterine cancer,30 prostate cancer,31, 32 testicular cancer,33 and liver cancer 34. The carcinogenic effects of BPA are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the controls of the study also showed an elevated baseline of tumor incidence when compared to controls in preceding studies. In contrast, other studies showed that dietary BPA exposure was insufficient to result in TC or aberrant lesions in the testes of Sprague-Dawley rats [157]. Long-Evans rats exposed to low doses of BPA perinatally showed an increase in the number of Leydig cells and altered androgen secretion, although the development of testicular neoplasias was unexplored [158].…”
Section: 00 Edcs In Testicular Development and Cancermentioning
confidence: 99%
“…For example, while Wistar-Furth rats exposed to 250 ug/kg BW/day of BPA show a shorter AGD and other developmental defects [163], Sprague-Dawley rats exposed up to 40 mg/kg BW/day of BPA did not show any changes in AGD [162]; studies have suggested that the Charles River Sprague-Dawley rat strain is relatively insensitive to estrogen and therefore, cannot be used to detect low dose effects of BPA [191]. Different inbred mouse strains also exhibit different sensitivity to EDCs, as seen in the case of BPA [157]. …”
Section: 00 Critical Analysis Of Edc Researchmentioning
confidence: 99%
“…Other applications include thermal paper, paper coatings and building materials [13]. BPA has been rated a high-volume production chemical with a global production rate of more than 5 Mt in 2015 [14]. According to the U.S. EPA [9], more than 1 million pounds of BPA leaches into U.S. environment every year.…”
Section: Introductionmentioning
confidence: 99%